2015
DOI: 10.1037/pas0000060
|View full text |Cite
|
Sign up to set email alerts
|

Defining early positive response to psychotherapy: An empirical comparison between clinically significant change criteria and growth mixture modeling.

Abstract: Several different approaches have been applied to identify early positive change in response to psychotherapy so as to predict later treatment outcome and length as well as use this information for outcome monitoring and treatment planning. In this study, simple methods based on clinically significant change criteria and computationally demanding growth mixture modeling (GMM) are compared with regard to their overlap and uniqueness as well as their characteristics in terms of initial impairment, therapy outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 46 publications
2
43
1
1
Order By: Relevance
“…In our study, the rate of participants showing early deterioration (16.1%, 66/409) was somewhat higher than in other studies (4.6%, [23]; 2.4%, [43]), yet more studies are required before conclusions regarding the risk of deterioration during Web interventions can be drawn. Participants who deteriorate early may be facing crisis and be in need of more immediate help than can be provided by an Web intervention.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…In our study, the rate of participants showing early deterioration (16.1%, 66/409) was somewhat higher than in other studies (4.6%, [23]; 2.4%, [43]), yet more studies are required before conclusions regarding the risk of deterioration during Web interventions can be drawn. Participants who deteriorate early may be facing crisis and be in need of more immediate help than can be provided by an Web intervention.…”
Section: Discussioncontrasting
confidence: 77%
“…Patterns of early change in depressive symptoms, measured by the PHQ-9 over the first 4 weeks of the Web intervention, were identified using piecewise growth mixture modeling (PGMM) [43]. GMMs are considered a conservative method of identifying early change patterns in comparison with rational definitions such as reliable or clinical significant change [44].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measures of psychological distress included the Outcomes Questionnaire (OQ‐45), and the Clinical Outcomes in Routine Evaluation (CORE). Only two studies used general psychological distress measures rather than disorder‐specific measures to assess symptom change (Lutz et al, ; Rubel et al, ), while two used a combination of both (Lutz, Stulz & Köck, ; Schibbye et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…As early as the 1980s, psychotherapy researchers have observed that the bulk of symptomatic improvement occurs within the 1st month of therapy, with 60% of total improvement in cognitive behavioral therapy for depression occurring by Week 4 (Rush, Kovacs, Beck, Weissenburger, & Hollon, ). Since then, numerous other studies have reported early response patterns across different mental health problems and psychological therapies (Bell, Waller, Shafran, & Delgadillo, ; Bradford et al, ; Delgadillo et al, ; Doyle, Le Grange, Loeb, Doyle, & Crosby, ; Gois et al, ; Hunnicutt‐Ferguson, Hoxha, & Gollan, ; Rubel et al, ).…”
Section: Introductionmentioning
confidence: 99%